1999
DOI: 10.1080/07315724.1999.10718859
|View full text |Cite
|
Sign up to set email alerts
|

Patterns in Child and Adolescent Consumption of Fruit and Vegetables: Effects of Gender and Ethnicity across Four Sites

Abstract: Ethnicity was related to fruit and vegetable consumption in Georgia and Minnesota. Consistent with prior studies, gender was related to fruit and vegetable consumption, with girls consuming more servings than boys; however, this was observed at one site only, Georgia. Consumption levels were similar to national estimates for children and varied by region. Further studies are needed using a single methodology to facilitate regional comparisons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
51
3
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 90 publications
(69 citation statements)
references
References 23 publications
14
51
3
1
Order By: Relevance
“…It was also noted in another study undertaken in the USA that fruit and vegetable consumption was greater in girls than in boys. 26 Alcohol consumption was significantly greater in male teenagers than females, in this Birmingham UK sample; this is in agreement with a USA study of 12-17-year-olds. 27 However, the current study showed a higher general consumption rate at 23%, in contrast to the US investigation which reported that 7.7% had already 'binged' on alcohol and 2.7% were heavy drinkers.…”
Section: Variable Significance (Sig)supporting
confidence: 79%
“…It was also noted in another study undertaken in the USA that fruit and vegetable consumption was greater in girls than in boys. 26 Alcohol consumption was significantly greater in male teenagers than females, in this Birmingham UK sample; this is in agreement with a USA study of 12-17-year-olds. 27 However, the current study showed a higher general consumption rate at 23%, in contrast to the US investigation which reported that 7.7% had already 'binged' on alcohol and 2.7% were heavy drinkers.…”
Section: Variable Significance (Sig)supporting
confidence: 79%
“…CUNNINGHAM-SABO AND LOHSE literature reporting that girls have higher preferences for fruits and, especially, vegetables, 10,11 we found no gender differences among the students in the present study.…”
contrasting
confidence: 46%
“…Some studies have obtained reasonable 24 hdr from 8 year old girls (Cullen et al, 2004), while food frequencies have elicited data similar to that from adults only with children 13 years and older (Field et al, 1999). Girls may be more reliable than boys (Prochaska, Sallis & Rupp, 2001); differences might be associated with ethnic groups (Reynolds et al, 1999); and underreporting has been associated with obesity (Briefel, Sempos, McDowell, Chien & Alaimo, 1997).…”
Section: Introductionmentioning
confidence: 99%